Effect of pulse energy on the dynamic development of spark-plasma-jet driven by nanosecond high-voltage pulse. (20th December 2017) - Tie, W; Zhang, Y; Meng, C; Zhang, Q; Yan, Z; He, P
Abstract: We investigated the spatial-temporal dynamics characteristics of the spark-plasma-jet (SPJ) in the nitrogen of 0.1 MPa at different pulse energies by fast photography and optical emission spectrum. The spark plasma generated by spark discharge can be rapidly sprayed out of the micro-incentive cavity within several tens nanoseconds under the action of electric field, and the spraying delay time reduces gradually with increase of pulse energy. The outlet velocity of SPJ reaches up to 10 4 m s −1 . After that, the propulsion velocity decreases dramatically by 1 or 2 orders of magnitude at 2 μ s. These two striking features were observed during the SPJ propulsion period. Firstly, there are two propulsion modes including 'plasma column' and 'plasma bullet' appearing in the development of SPJ successively. The conversion from plasma column to plasma bullet is slowed down with the increase of discharge current duration. Secondly, the inner form of SPJ exhibits the 'halo', 'core-halo' and 'tree' patterns respectively at the pulse energies of 1.6 J, 32 J and 160 J. Furthermore, the distribution morphology of SPJ obviously has flow field features. In order to accurately estimate the spatial-temporal distribution of electron parameters by optical emission spectroscopy diagnosis, the electron temperature was calculated by the Boltzmann plot method and continuum radiation, respectively, and the electron density was calculated by the Saha equation and Stark broadening respectively. The results show that the electron temperature and electron density of SPJ are 1.7 eV ∼ 2.9 eV and 8.5 × 10 16 /cm 3 ∼ 1.0 × 10 18 /cm 3 respectively in different conditions. These results provide some fundamental knowledge about the dynamic development of SPJ.